Application of a logical-probabilistic method of failure and fault trees for predicting emergency situations at pressure hydraulic facilities (the case of Kakhovka hydroelectric complex) - Stefanyshyn, Dmytro; Benatov, Daniel (Eastern-European Journal of Enterprise Technologies, 2020)
The problem of forecasting emergency situations at hydraulic facilities of a hydroelectric complex, forming its pressure waterfront, based on the application of a logical-probabilistic approach is considered. The relevance of the studies and their practical significance are determined by the need to assess the compliance of the safety of hydraulic facilities with international safety standards and current national legislation. Therefore, the reports on the environmental impact assessment of hydraulic facilities should present the results of assessing the additional risk of emergency situations at the hydroelectric complex. This assessment, in turn, requires an analysis of the probability of accidents at the hydroelectric complex before and after new construction. In the present study, using the example of the Kakhovka hydroelectric complex (Ukraine), the systemic nature of possible causes of accidents at pressure hydraulic facilities as part of hydroelectric complexes is found. An accident at a hydroelectric complex is considered as a complex natural and man-made event, which can be associated with various natural and man-made factors. The total (generalized) probability of an accident at the hydroelectric complex is estimated by the logical-probabilistic method of failure and fault trees based on a deductive approach. The upper limit estimates of the probability of accidents at individual hydraulic facilities of the hydroelectric complex and the generalized estimate of the probability of an accident at the hydroelectric complex as a whole are calculated. It is found that the probability of an accident depending on the hydraulic facility of the hydroelectric complex can vary. In the case of the Kakhovka hydroelectric complex, it varies from 2.1×10–6, year–1, at the run-of-river earth dam, to 5.6×10–6, year–1, at the spillway dam. The total probability of an accident at the hydroelectric complex is 2.35×10–5 emergency events per year. However, these estimates do not exceed the permissible value of 5×10–5, year–1, which is regulated for hydraulic facilities of the corresponding consequence class. Thus, it is concluded that the current reliability and safety of the hydraulic facilities of the Kakhovka hydroelectric complex can be recognized as sufficient